PERIOD CHANGES IN THE GROUP OF ALGOL-TYPE BINARY SYSTEMS WITH ASYNCHRONOUS ROTATION OF THE MAIN COMPONENT - Glazunova, L. V. (Одеські астрономічні публікації, 2017)
The period change for the group Algol-type binaries with an asynchronous rotation of a main component is studied. Under the observational data, available in the literature, a general tendency in change of periods of these systems was obtained. As against to the majority of Algols, for 6 of 8 systems of this group the period decrease is observed for last decades.